Faktor Risiko Mortalitas Pasien Geriatri yang Dirawat Di ICU RSUP Dr. Sardjito Yogyakarta - Hendra, Maijoni; Akhmad Yun; Widodo, Untung (Jurnal Komplikasi Anestesi, 2022)
Background: Nowadays, many geriatric patients need intensive care. In intensive care geriatric patients will show geriatric syndromes such as delirium, sensory disturbances and frailty which are closely related to morbidity and mortality. Until now in Indonesia there has been no specific study that examines the risk of death in geriatric patients treated in the ICU. Objective: To identify the risk factors that influence the mortality of geriatric patients in the ICU, as a reference material in the management of geriatric patients in the ICU. Method: This study is a retrospective cohort observational study. The study sample consisted of 162 patients who were treated at ICU Dr. Sardjito General Hospital from 1 January 2020 to 31 December 2020. The identified risk factors were then analyzed and tested using the student's t-test for numerical data and the chi square test for categorical data. The results of the analysis with p <0.25 were then carried out with a logistic regression test. Variables with p <0.05 in multivariate analysis were considered significant. Data were analyzed statistically with the SPSS 25.0 application. Results: Factors identified as risk factors for mortality in geriatric patients in the ICU Dr. Sardjito General Hospital were kidney comorbidities in the form of acute kidney injury and chronic kidney disease (p=0.019, OR 0.364), the use of inotropic vasopressor drugs such as dopamine, dobutamine, norepinephrine, epinephrine, vasopressin (p=0.003, OR 0.277) and the use of mechanical ventilation (p=0.004, OR 0.890) were the variables that had the most significant effect simultaneously on the mortality of geriatric patients in the ICU. Conclusion: The identified risk factors for geriatric patients’ mortality in the ICU of Dr. Sardjito General Hospital are renal comorbidities, the use of invasive mechanical ventilation and the use of inotropic and vasopressor drugs.